Education on Balanced Nutrition and Healthy Snacks in the School Environment to Prevent Nutritional Problems among Adolescents - Nurbaya, Nurbaya; Najdah, Najdah; Irwan, Zaki (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Around 12% of male and 23% of female adolescents experience anemia due to iron deficiency. Several habits cause nutritional problems in adolescents are not always having breakfast, most adolescents do not consume enough fibre, fruit vegetables, and consuming flavorful foods. In addition, adolescents also tend to adopt a sedentary lifestyle, resulting in less physical activity. This community service activity aimed to increase adolescents’ knowledge about balanced nutrition and healthy snacks at school. The methods used in this activity were FGD, counseling, and simulation. The targets were students, teachers, and canteen managers, totaling 30 people. The training was carried out in April-May 2023 at SMAN 2 Mamuju. The evaluation was conducted through questions and answers and a simulation of reading nutritional information on food packaging. Results: Participants can determine healthy and safe foods to be consumed and read the nutritional information on food packaging. The canteen manager can sort out nutritious food for the school canteen. Counseling on balanced nutrition and healthy snacks can increase adolescents' knowledge about nutrition and healthy snacks in the school environment. The school and related stakeholders must provide balanced nutrition messages in the schools' teaching and learning process.